2016
DOI: 10.1149/2.0251604jss
|View full text |Cite
|
Sign up to set email alerts
|

Review—Properties of Intrinsic Point Defects in Si and Ge Assessed by Density Functional Theory

Abstract: During the last decade, considerable progress has been made in understanding the properties and behavior of the vacancy V and self-interstitial I in silicon (Si) and germanium (Ge) crystals. This is to a large extent due to the maturing of density functional theory (DFT) calculation techniques and the increase of computing power enabling to calculate not only the formation and migration energies of V and I, but also the interaction with impurities and with crystal surfaces. Furthermore, the impact of internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 132 publications
5
28
0
1
Order By: Relevance
“…Table summarizes the E b of the most stable structures calculated by Si 64‐atom and 216‐atom cubic cells. E b obtained by the previous studies are also summarized . It is found that, for (i) C s + I → C i , (ii) V + V → V − V , (iii) C i + O i → C i − O, (iv) V + O i → V − O i , (v) C i + C s → C i − C s , (vi) P + V → V –P, (vii) P + C i → P–C i , the calculated E b well agreed with that obtained in the previous studies in the range of 0.3 eV.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Table summarizes the E b of the most stable structures calculated by Si 64‐atom and 216‐atom cubic cells. E b obtained by the previous studies are also summarized . It is found that, for (i) C s + I → C i , (ii) V + V → V − V , (iii) C i + O i → C i − O, (iv) V + O i → V − O i , (v) C i + C s → C i − C s , (vi) P + V → V –P, (vii) P + C i → P–C i , the calculated E b well agreed with that obtained in the previous studies in the range of 0.3 eV.…”
Section: Resultssupporting
confidence: 84%
“…On the basis of these results, we performed calculations related to the structural changes of lifetime‐control defects; the interaction of the candidate complexes, found by (1) and (2), with V or P composed of lifetime‐control defects. As it will be cited and compared in this paper, a number of DFT calculations have been performed for the various defects related to vacancy, phosphorous, oxygen and carbon etc in Si crystals . However, from the viewpoint of the influence on lifetime control defects, systematic calculations have not been reported to clarify the candidates to affect the lifetime‐control defects.…”
Section: Introductionmentioning
confidence: 99%
“…3). During these visits, many young Japanese researchers and students benefited from the fruitful discussions with Jan. From 2006, several common research programs have been undertaken, resulting in 21 joint published papers [21,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Modeling Point Defectsmentioning
confidence: 99%
“…Thus, defects such as VO, C i O i , C i C s , and on anneals V n O m and C i O i Si I clusters [9,12,[40][41][42][43][44] affect the production and the balance of the V and the Si I 's concentrations. Since these primary defects play important role in O and C aggregation processes [9][10][11][12][13][14][45][46][47][48] it is necessary to study such processes in irradiated material. Notably, VO and VO 2 defects have been suggested [49] to act as nucleation sites for O precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering co-doping pairs (C, Sn) in Si will help us gain a more complete understanding of mechanisms that govern O and C precipitation processes as well as the ways that Sn isovalent dopants affect these processes. Importantly, since V and Si I play [61][62][63][64][65][66][67] a key role in the O and C precipitation processes we can reversibly deepen our understanding on the mechanisms through which these primary defects affect the agglomeration of O and C impurities in Si treated at elevated temperatures. Also it could enhance the opportunities for technological improvements of Si providing an engineering strategy for thermal defects that could be employable to analogous systems.…”
Section: Introductionmentioning
confidence: 99%